The Profile Analysis of Prospective Elementary Teacher’ Scientific Literacy as an Initial Strategy to Conduct Science Courses - Hanifah Mulyani; Rizki Hadiwijaya Zulkarnaen; Yanda Hernisa (Postgraduate, University of Mataram, 2025)
Scientific literacy is one of the most important aspect students should have to help them in making decisions toward any problem and to understand all the changes that probably occurred in society. According to last PISA results, scientific literacy of Indonesian students categorized as low. Educational institutions and teachers have responsibilities to improve this scientific literacy. This research was conducted to analyze the scientific literacy of prospective elementary teachers. Descriptive qualitative method was used and involve research subjects as much as 120. The data taken by giving scientific literacy test. questionnaire, and interview to some research subjects. The data analysis was inductive technique, consisted of collecting, reducing, displaying, and verifying data. The result was was 47,5 and categorized as moderate. This result indicated that the lecturer may implement learning strategies where science process skill of students could be well-developed, integrate science and mathematics courses, and engage students in scientific reading